Peran Biomarker Darah terhadap Distribusi Lemak Tubuh pada Perempuan Dewasa : Analisis Korelasi Hematologis dan Metabolik - Christian Wijaya; Alexander Halim Santoso; Bryan Anna Wijaya (Jurnal Kesehatan Amanah, 2025)
Introduction: Subcutaneous fat distribution in adult women changes significantly with age, particularly during menopausal transition. This modulation is closely linked to hormonal alterations and may be reflected through blood biomarkers. Methods: A cross-sectional study was conducted to analyze the relationship between age and blood biomarkers (hemoglobin, fasting glucose, HDL, and uric acid) with subcutaneous fat thickness at three body sites (biceps, triceps, and suprailiac) in adult women. Pearson correlation tests were used to assess associations between variables. Results: A significant positive correlation was found between age and biceps fat thickness (r = 0.112; p = 0.044). Hemoglobin showed a consistent positive correlation with fat thickness across all sites. Fasting glucose correlated positively with triceps fat (r = 0.109; p = 0.050), and uric acid was positively associated with triceps and suprailiac fat. HDL exhibited a significant negative correlation with suprailiac fat (r = -0.180; p = 0.001). Conclusion: Blood biomarkers hold potential as non-invasive indicators for tracking age-related subcutaneous fat redistribution. This approach could enhance early detection of metabolic risk in adult women and support preventive and integrative clinical strategies.